Dynamic myosin phosphorylation regulates contractile pulses and tissue integrity during epithelial morphogenesis - Vasquez, Claudia G. (The Rockefeller University Press, 2014)
Apical constriction is a cell shape change that promotes epithelial bending. Activation of nonmuscle myosin II (Myo-II) by kinases such as Rho-associated kinase (Rok) is important to generate contractile force during apical constriction. Cycles of Myo-II assembly and disassembly, or pulses, are associated with apical constriction during Drosophila melanogaster gastrulation. It is not understood whether Myo-II phosphoregulation organizes contractile pulses or whether pulses are important for tissue morphogenesis. Here, we show that Myo-II pulses are associated with pulses of apical Rok. Mutants that mimic Myo-II light chain phosphorylation or depletion of myosin phosphatase inhibit Myo-II contractile pulses, disrupting both actomyosin coalescence into apical foci and cycles of Myo-II assembly/disassembly. Thus, coupling dynamic Myo-II phosphorylation to upstream signals organizes contractile Myo-II pulses in both space and time. Mutants that mimic Myo-II phosphorylation undergo continuous, rather than incremental, apical constriction. These mutants fail to maintain intercellular actomyosin network connections during tissue invagination, suggesting that Myo-II pulses are required for tissue integrity during morphogenesis.